Ultrastructural Mechanisms of Aposporous Embryo Sac Initial Cell Appearance and Its Developmental Process in Gametophytic Apomicts of Guinea Grass (Panicum maximum) - Chen, Lanzhuang; Guan, Liming (IntechOpen, 2012)
None